Green Marketing Strategies and Consumer Behavioral Scenario in Bangladesh Perspective - Md. Sohel Rana (International Journal of Social Service and Research, 2026)
Green marketing has emerged as a significant strategic tool for businesses worldwide, especially as environmental awareness and sustainability concerns continue to grow. In Bangladesh, where environmental challenges such as pollution, climate change, and resource depletion are increasingly pressing, green marketing offers both an opportunity and a responsibility for businesses. This research investigates the impact of green marketing strategies on sales performance, market share, and brand profitability, focusing on the Bangladeshi business context. Using a mixed-methods approach, the study combines quantitative data from 200 consumer surveys with qualitative insights from 10 interviews with marketing professionals in Dhaka, Khulna, and Chattogram. The findings reveal that green marketing practices, such as eco-friendly product design, sustainable packaging, environmental branding, and corporate social responsibility (CSR) initiatives, positively influence consumer behavior, foster brand loyalty, and contribute to improved financial outcomes. The study considers 10 independent variables to measure their effects on consumers’ monthly purchasing preferences. The results demonstrate a significant correlation between effective green marketing efforts and increases in sales and market share. The study concludes that, although green marketing is still evolving in Bangladesh, it holds substantial potential for enhancing both environmental sustainability and business performance. Recommendations are provided for businesses, policymakers, and marketers to create more impactful and trustworthy green marketing strategies. The multiple regression results show that RMI, RED, SPA, GPP, and GMS have positive and significant relationships with consumers’ purchasing preferences.